Pengembangan Aplikasi Messaging Berbasis Android Untuk Jaringan Intranet Kampus Universitas Brawijaya - Achmad Yazi'; Herman Tolle; Mahardeka Tri Ananta (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Messaging applications with the internet today is often done by mobile devices users for communicating. However, messaging applications that use the internet, especially in UB campus environment have problems. Wi-Fi users and internet access needs in large campus environments are often mobile devices can only connect with Wi-Fi only and log into a campus intranet network without being able to access the internet. So in this research, messaging application developed that can be used on intranet network of UB campus without using internet connection. This research used pull messaging method with the server placed in the Faculty of Computer Science Brawijaya University. We then tested the usability level using the Questionnaire System Usability Scale (SUS) and availability level. The results showed the value of SUS testing is 84.67% and availability score is 100%. From the results of usability and availability testing showed that this messaging application has a good usability level and can run on the condition both the internet is available or not available